RNA-based therapies for colorectal cancer: targeting the β-catenin pathway via microbiota -modulated miRNAs - Prabhakaran, Rajkumar; Muthu, Ramkumar; Manickam, Rajkumar; Subramanian, Venkatesh; Mahendran, Karthikeyan (Frontiers in Molecular Biosciences, 2026)
Colorectal cancer (CRC) is a significant problem with worldwide public health consequences. One key factor in the genesis and progression of CRC is the aberrant upregulation of the Wnt/β-catenin signaling pathway. Inhibitors designed to target β-catenin directly have not been effective in clinical trials, whereas miRNAs have been shown to regulate post-transcriptional components of the Wnt/β-catenin signaling pathway. Microorganisms in the gut also produce miRNAs that regulate CRC-related genes at the post-transcriptional level, including those involved in the Wnt pathway. An example is Fusobacterium nucleatum, which increases expression of the oncogenic miR-135b/miR-21, thereby inhibiting the expression of the tumor suppressors APC/PTEN and stabilizing β-catenin. This results in increased MYC expression. Another example is Bacteroides fragilis, which reduces miR-200c expression, thereby promoting epithelial-mesenchymal transition (EMT). However, this increase in EMT is countered by miR-145 and miR-203, which are upregulated by probiotic treatment, and these miRNAs inhibit the oncogenes CTNNB1 and LEF1. There are currently several reviews that address subsets of the pathways involved in the dysregulation of β-catenin, as well as the therapeutic potential of miRNAs, and reviews that address microbiota interaction with CRC, but none that combine these elements within the framework of a mechanistic axis for the CRC microbe-miRNA-β-catenin-tumor phenotype, nor therapies based upon that axis/mechanism. This review examines the β-catenin signaling pathway in CRC and its regulation by miRNAs. It summarizes the roles of miRNAs in CRC, highlights oncogenic and tumor-suppressive miRNAs, and outlines specific miRNAs that are targets of the β-catenin pathway. It also covers microbiota-host interactions, including bidirectional links between gut microbes and miRNAs, effects on intestinal homeostasis, and microbial metabolites that alter miRNA expression. Recent advances in RNA-based therapeutic strategies and progress in clinical trials are included to frame the current translational relevance.